PENGARUH KEPUASAN KERJA, INNOVATIVE WORK BEHAVIOR, DAN DUKUNGAN REKAN KERJA TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN BANTUL: Indonesia - Sanjaya, Machmud Zain Alwi; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Jurnal Manajemen Terapan dan Keuangan, 2024)
Dinas Perhubungan Kabupaten Bantul is a government organization that operates in the transportation sector, which has an important role in society. Optimizing individual performance is still a concern in employee work behavior within government organizations. Performance factors can be caused by job satisfaction, innovative work behavior, and coworker support. So this study aims to determine the effect of job satisfaction, innovative work behavior, and coworker support on employee performance at Dinas Perhubungan Kabupaten Bantul. This research is a quantitative study that uses primary data collection with questionnaire instruments. This study involved 45 respondents whose data were taken using accidental sampling, and the number of respondents was determined by the Slovin formula. The results showed that job satisfaction has no effect on employee performance, innovative work behavior also has no effect on employee performance, and coworker support has a significant positive effect on employee performance. Strengthening and maintaining a work ecosystem that facilitates good relationships between fellow employees is a task for the organization if it takes policies to improve employee performance.